Un établissement rural de La Tène finale à Couesmes, La Tesserie (Indre-et-Loire) - Bénédicte Quilliec; Jean-Marie Laruaz (Revue Archéologique du Centre de la France)
The La Tesserie site (Couesmes, Indre-et-Loire) was found during an archaeological evaluation in 2007. This site is a rural dwelling located on 2.5 ha on the route of a future departmental road (RD766, Château-la-Vallière). Excavations were carried out during the winter 2008-2009 by Indre-et-Loire’s Departmental Archaeological Service (SADIL), managed by Bénédicte Quilliec. The settlement from the end of La Tène is organized around a quadrangular ditch (about 60 m side) with different kinds of constructions (structures, functions, sizes)Knowledge of this kind of site is still lacking because it depends directly on the archaeological survey as in the remainder of the Indre-et-Loire department. Therefore the excavation of La Tesserie was a great opportunity because the entire surface covered by the settlement was excavated providing useful information. In the light of the new data resulting from the study of several assemblies coming from varied structures, it is possible to better define the architectural constructions and identify the ceramic, bronze and iron furnishings and also animal bones and seeds. In addition this study enabled comparison to be made with various similar sites in the north of France.